Comparative analysis of the profile of circulating microRNAs in the blood plasma of patients with gliomas - D. Yu. Gvaldin; N. A. Petrusenko; E. E. Rostorguev; S. N. Dimitriadi; S. E. Kavitskiy; N. N. Timoshkina (Исследования и практика в медицине)
Against the background of modest successes in the development of new diagnostic and therapeutic tools to improve the survival of patients with glial brain tumors, early diagnosis of this pathology remains relevant. Endogenous noncoding miRNAs that regulate the expression of target mRNAs have become attractive targets for the development of circulating biomarker-based assays, because sample acquisition does not require invasive sampling such as biopsy.Purpose of the study. To determine the levels of circulating microRNAs in the blood plasma of patients with glial tumors, meningiomas and apparently healthy donors, using high-output sequencing.Material and methods. 26 blood plasma samples were selected from the biobank data base of the National Medical Research Center for Oncology, and the total RNA was studied using the NGS sequencing method. The sample included: 2 cases of oligodendroglioma (grades 2–3), 6 – astrocytomas of 2–4 degrees of malignancy, 7 – glioblastomas of 4 degrees of malignancy, 7 – benign neoplasms (meningiomas), 4 – control (conditionally healthy donors).Results. During the primary analysis, a pool of 71 differentially expressed microRNAs was identified, the expression of which was tumor-specific: 20 microRNAs for glioblastoma, 4 microRNAs for astrocytoma, 23 microRNAs for oligodendroglioma, 24 microRNAs for meningioma. At the same time, 47 microRNAs showed increased levels in the blood plasma compared to the control group, 15 showed a corresponding decrease in levels. A comparative analysis identified microRNAs that specifically differentiate each tumor type.Conclusion. The results obtained seem promising and set the vector for further research, which will include expanding the sample and validating the identified biomarkers to determine their diagnostic value.